Societal Impact of Special Industrial Incentives Package: Managerial Perceptions - Chaudhary, Rashmi (Prabandhan: Indian Journal of Management, 2012)
This paper aims to examine the relationship between select social parameters and Special Industrial Incentives Package (SIIP) granted to Himachal Pradesh, one of the eleven special category states eligible for central assistance, in January 2003. Historical evidence brings forward the fact that incentive packages fuel the industrial growth of an area, which ultimately leads to social development. Moving on the same tack, Government of India announced incentive packages to underdeveloped states, an important fiscal measure for achieving balanced regional development. In this backdrop, the present paper is an attempt to analyze the socio-economic development in Himachal Pradesh attributable to SIIP. Results of data analyses reveal that government incentives and concessions have played a key role in the overall development of the state. It was concluded that on the one hand, such incentives have positively affected social infrastructural and economic facilities in the study state, but on the other hand, negative ecological impacts were also observed. Evidence of the study is relevant to policymakers designing tax incentives for industrially backward states. Further, the study has implications for the industrially backward states, as it will help in reviewing the impact of government incentives and concessions extended to these states for better monitoring. Findings of the paper highlight the need for studying SIIP as a correlate of socio-economic development for better understanding of issues relating to industrial development of an industrially backward area.